Application of the ecosystem service concept at a small-scale: The cases of coralligenous habitats in the North-western Mediterranean Sea. (January 2019) - Thierry de Ville d'Avray, L.; Ami, D.; Chenuil, A.; David, R.; Féral, J.-P.
Abstract: The understanding of ecosystem services is essential to support sustainable use and preservation of ecosystems. Coralligenous habitats, main contributors of the Mediterranean marine biodiversity, are yet understudied in term of services provided. This study presents an original small-scale approach to investigate the services provided by coralligenous habitats of a French study area consisting of two marine sites (Marseille and Port-Cros sites) in order to cover two contrasted anthropogenic pressure despite the small-scale. Our results are based on the opinions of 43 experts who ranked 15 services in terms of existence and level of importance for human well-being: supporting ecological functions were considered the most important, then provisioning and cultural services. Regulating services were considered uncertain due to a lack of knowledge. The small-scale approach highlighted a need for a referential frame to determine the existence of services (e.g. geographical and temporal scales, benefits and beneficiaries levels). Highlights: Coralligenous habitats provide at least 10 ecosystem services according to experts. The main services are: food provisioning, diving sites, potential of discovery. Scientific knowledge is missing to identify regulation services. The number of beneficiaries is the criterion most used to rank services.